2017
DOI: 10.1016/j.ijdevneu.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Altered visual repetition suppression in Fragile X Syndrome: New evidence from ERPs and oscillatory activity

Abstract: Fragile X Syndrome (FXS) is a neurodevelopmental genetic disorder associated with cognitive and behavioural deficits. In particular, neuronal habituation processes have been shown to be altered in FXS patients. Yet, while such deficits have been primarily explored using auditory stimuli, less is known in the visual modality. Here, we investigated the putative alteration of repetition suppression using faces in FXS patients compared to controls that had the same age distribution. Electroencephalographic (EEG) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 88 publications
2
21
0
Order By: Relevance
“…A decreased ability to habituate has been described in a fraction of ASD individuals (911), but has not been connected yet to specific genetic defects, with a single exception. Recently, two independent studies demonstrated habituation deficits in patients with Fragile X syndrome, the most common monogenic cause of intellectual disability (ID) and ASD (12, 13), confirming previously reported habituation deficits in Fmr1 KO mice (14, 15). Habituation deficits have also been reported in a limited number of other ID or ASD (ID/ASD) disease models (1619).…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…A decreased ability to habituate has been described in a fraction of ASD individuals (911), but has not been connected yet to specific genetic defects, with a single exception. Recently, two independent studies demonstrated habituation deficits in patients with Fragile X syndrome, the most common monogenic cause of intellectual disability (ID) and ASD (12, 13), confirming previously reported habituation deficits in Fmr1 KO mice (14, 15). Habituation deficits have also been reported in a limited number of other ID or ASD (ID/ASD) disease models (1619).…”
Section: Introductionsupporting
confidence: 80%
“…Still, this latter phenotype category can result from other defects than improved habituation, and will be investigated elsewhere. In this study we focus on habituation deficits (3), corresponding to the phenotype that has been shown in ID and ASD (913).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gamma synchronization facilitates neural communication and increases the effective output of presynaptic (Bastos et al, 2015; Fries, 2005, 2009, 2015; Ni et al, 2016; Rigoulot et al, 2017; Vinck et al, 2013). Therefore, synchronization of V1 neural activity in the gamma range is thought to enhance the effective output from the primary visual cortex to upstream cortical areas, thus affecting visual perception.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in genetics and neuroscience clearly demonstrate that behavioral symptoms of ASD and other neurodevelopmental disorders may stem from cardinally different genetic and molecular etiologies that cause either increases or decreases in the E/I ratio (Lee et al, 2017; Nelson and Valakh, 2015). Given the heterogeneous nature of ASD (Gillberg, 2010; Jeste and Geschwind, 2014; Tordjman et al, 2018), the abnormal capacity to regulate the E/I balance in the visual cortex could characterize only a proportion of ASD individuals, as well as, e.g., patients with fragile X syndrome who are often hypersensitive to visual stimuli and are suggested to have elevated neural excitability of the visual cortex (Rigoulot et al, 2017; Schneider et al, 2009; Sinclair et al, 2017; Van der Molen et al, 2012). Considering the reliable correlation between sensory sensitivity and GSS (Fig.…”
Section: Discussionmentioning
confidence: 99%